Viscometric and Thermodynamics Study of uni-bivalent Mixed Electrolytes in Aqueous Solutions at 293.15, 303.15 and 313.15K - Durgesh Gautam; Varsha Sharma; Mukhtar Singh (International Journal of Research in Chemistry and Environment (IJRCE), 2017)
Viscosities (η) and apparent molar volumes (Vf) of the solutions of uni-bivalent mixed electrolytes in aqueous solutions have been determined at 293.15, 303.15and 313.15K. It is seen that the plots of ήrel-1/√y verses √y are linear, from which the values of coefficients A and B have been obtained by the method of least squares. The values of coefficient A are positive for the mixed electrolytes (NH4)2C2O4 + K2C2O4, Na2SO4 + K2SO4 and (NH4)2SO4 + K2SO4. The negative values of B in the case of Na2SO4 + K2SO4 and (NH4)2 SO4 + K2SO4 show the presence of strong ion-ion interactions in the aqueous solution of these mixed electrolytes. In each case the values of A tend to decrease with the rise of temperatures which suggests further weakening of ion-ion interactions at elevated temperatures. The values of B are positive which tend to increase more positive with the rise of temperature there by suggesting the presence of strong ion-solvent interactions, which becomes stronger at elevated temperatures. The variation of with. y, fraction of ionic strength due to the first electrolyte in the mixture of two electrolytes at different temperatures is linear. From ή and VΦ data the values of coefficients A and B of Jones -Dole equation and that of V and Sv of Masson's equation have been obtained. Besides the activation thermodynamic quantities Δμ20# , ΔH20#and ΔS20# of viscous flow have also been calculated for the mixed electrolytes in aqueous solutions. It is seen that the values of Δμ20# are much larger as compared to those of Δμ10# for all the uni-bivalent mixed electrolytes. The values of TΔS20# are negative while those of ΔH20# are positive and that ΔH20# > TΔS20#, thereby suggesting that ion-solvent interaction for the mixed electrolyte system, are nearly complete in the ground state. Further these are the values of TΔS20# and ΔH20# indicate the transition state is associated with the bond breaking and increase in order.